208k views
4 votes
Hellllpppp Pleaseeeeee

Hellllpppp Pleaseeeeee-example-1
User Rwallace
by
5.8k points

2 Answers

3 votes

Answer:

Statement 1 & Statement 3

Explanation:

4 ÷ 10/3

4 × 3/10

12/10

6/5

f(x + 1) = (6/5) × f(x)

f(x) = (10/3) × (6/5)^(x-1)

f(x) = (10/3) × (5/6) × (6/5)^x

f(x) = (25/9) × (6/5)^x

The domain is all natural numbers and the range is real numbers

User Jhodges
by
5.2k points
4 votes

Explanation:

Step 1: Find the correct answer

Option A is correct because if you plug in the numbers...


f(0 + 1) = (10)/(3)
f(1)=(10)/(3)


f(1 + 1) = (6)/(5) * (10)/(3)
f(2)=4


f(2 + 1) = (6)/(5) * (4)/(1)
f(3) = (24)/(5)


f(3 + 1) = (6)/(5) * (24)/(5)
f(4) = (144)/(25)

Also, Option C is correct because if you plug in the numbers...


f(1) = (10)/(3)((6)/(5))^(^1^-^1^)
f(1) = (10)/(3) * 1
f(1)=(10)/(3)


f(2) = (10)/(3)((6)/(5))^(^2^-^1^)
f(2) = (10)/(3)*(6)/(5)
f(2) = 4


f(3) = (10)/(3)((6)/(5))^(^3^-^1^)
f(3) = (10)/(3)*(36)/(25)
f(3) = (24)/(5)


f(4) = (10)/(3)((6)/(5))^(^4^-^1^)
f(4) = (10)/(3) * (216)/(125)
f(4) = (144)/(25)

The reason why option B is not correct is because when you plug in a number, the output is incorrect. The reason why Option D is not correct is because the domain does not include negative numbers which means that the domain is all natural numbers. The reason why Option E is not correct is because the range is all real numbers and not just natural/positive numbers.

Answer: Options A, C

User Michiel Kalkman
by
5.8k points